Nerves Around the Shoulder: What the Radiologist Should Know? - Afarine Madani; Viviane Creteur (Journal of the Belgian Society of Radiology, 2017)
Peripheral neuropathies of the shoulder are common and could be related to traumatic injury, shoulder surgery, infection or tumour but usually they result from an entrapment syndrome. Imaging plays an important role to detect the underlying causes, to assess the precise topography and the severity of nerve damage. The key points concerning the imaging of nerve entrapment syndrome are the knowledge of the particular topography of the injured nerve, and the morphology as well signal modifications of the corresponding muscles. Magnetic Resonance Imaging best shows these findings, although Ultrasounds and Computed Tomography sometimes allow the diagnosis of neuropathy.